Role of procalcitonin, Il-6 and C- reactive protein in suspected cases of sepsis - Shiwangi Sharma; Nandini Duggal (Wolters Kluwer Medknow Publications, 2019)
Objectives: To study the role of serum procalcitonin as a diagnostic biomarker in sepsis and to compare it with other sepsis markers (IL-6, CRP) in patients of suspected sepsis. Materials and Methods: A total of 80 patients were included in this study from ICU and each patient was investigated for serum Procalcitonin, Interleukin-6 and C-reactive protein levels by ELISA along with blood cultures by BacT/Alert system. Result: Procalcitonin along with CRP is a better diagnostic tool for sepsis.